Trg delovne sile in sestava delavskega razreda - Močnik, Rastko (Teorija in praksa, 2011)
This text argues that the expression "the labour power market" is not a theoretical concept but an ideological notion and proposes to replace it with the concept of "the social composition of labour power". This concept is not limited to the presumed mechanism of supply and demand, but grasps the capital relation of production as it is complexly structured within concrete social formations dominated by the capitalist mode of production. The concept theoretically determines the articulation of components that, at an ideological glance, appear as a heterogeneous aggregate of numerous institutional and practical dimensions (legal regulations, technological determinations, organisation of labour processes and practices of governance, practices of collective co-operation at the work place, educational structure and system and other ideological apparatuses etc.). It shows the logic that, by complex and contradictory structuring, constitutes eventual "markets" and, most importantly, production practices in their complex efficiency that propels the entire process of social production and reproduction under the domination of capital.
Keywords: Capitalism; Kapitalizem; Labor market; Trg dela; Delavski razred; Working class; Class struggle; Razredni boj; trg delovne sile; ideologija